"Shared" Information in the Age of Big Data: Exploring Sentiment Expression Related to Nuclear Energy on Twitter. (June 2016) - Kim, Jiyoun; Brossard, Dominique; Scheufele, Dietram A.; Xenos, Michael
Living in an age of big data, this study explores (a) how much certain online information is shared by media users and (b) what sentiments do social media users predominantly express on Twitter. Quantitative findings indicate that after the 2011 nuclear disaster at Fukushima Japan, the amount of nuclear energy–related tweets that were linked to outside information far outnumbered tweets containing no external link. Results also indicate that the predominant tone in these tweets was one of pessimism about nuclear energy.